EMPOWERMENT OF PUBLIC HEALTH OF SINARMUKTI VILLAGE THROUGH THE DISTRIBUTION OF MASKS, HAND SANITIZERS AND DISINFECTANT SPRAYING DURING THE COVID-19 PERIOD: PEMBERDAYAAN KESEHATAN MASYARAKAT DESA SINARMUKTI MELALUI PEMBAGIAN MASKER, HAND SANITIZER DAN PENYEMPROTAN DISINFEKTAN PADA MASA COVID-19 - Imel Christ Monica; Anton Nasrullah; Rani Puspa; Putri Ainia Salsabila; Sarah Caesarani; Roihatul Mawaddah; Siska Lestari (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2022)
This Community Service (PKM) aims to educate the hamlet community in Sinarmukti Village, Baros District, Serang-Banten Regency about the importance of cleanliness, including washing hands or using hand sanitizers and masks before and after activities outside the home to break the chain of transmission of Covid - 19. This PKM activity is community empowerment by distributing masks, hand sanitizers, and spraying disinfectants in Sinarmukti village. This service involves group KKM students, field supervisors, the community of Sinarmukti Village, Baros District, Serang-Banten Regency. The conclusion of this community service activity is to provide education and empowerment to the community of Sinarmukti Village, Baros District, Serang-Banten Regency about the importance of wearing masks and washing hands with soap or hand sanitizers to break the chain of the spread of Covid-19 by providing hand sanitizer masks and spraying disinfectants. In the village of Sinarmukti. Baros District, District. Serang-Banten